Machine Learning Aided Diagnosis Designing and Evaluating Vitas, a Virtual Intelligent Tool for Assessment and Symptom Check, Using the DDXPLUS Dataset - Saet, Myra F.; Landingin, John Vincent N.; Jamir-Domingo, Jeff Louine T.
ABSTRACT